Correct electrostatic treatment of noncovalent interactions: the importance of polarization. (1st December 2014) - Clark, Timothy; Politzer, Peter; Murray, Jane S.
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" id="wcms1210-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>